Labour's First Year : 1945-46 (London : Common Wealth Publications Committee, 1946)
1946 1946 1940s 27 pages HEALTH SERVICE AS A BIRTHRIGHT In few spheres of human affairs are socialist principles more obviously applicable than in the organisation of our forces in the unending fight against disease, an enemy common to all mankind. At last we have before us, in outline, proposals inspired by this ideal. It is our duty to examine these proposals with the greatest attention and to decide how far they can be expected to succeed in their avowed purpose. For better or for worse the Bill now passing through parliament is generally regarded as a socialist measure and any failure in this most favourable held would reflect very seriously on future socialist proposals. Scope of the Service The National Health Service Bill places on the Minister of Health the duty of providing "a comprehensive health service for the improvement of the physical and mental health of the people of England and Wales, and for the prevention, diagnosis and treatment of illness." The Service will be available to all irrespective of financial means, age, sex, insurance qualification, etc. Although the Service will be in part financed by insurance contributions, people in arrears will not thereby be disqualified from receiving the benefits of the scheme. Organisation The Minister will organise and administer the Service through three channels as follows :— 1. Direct Responsibility of the Minister. Hospital and specialist services. Blood transfusion services. Bacteriological laboratories for the control of epidemics. (Actual administration of the hospitals will be through regional and local bodies appointed by the Minister after consultation with various interested bodies). 10 15X/2/98/21